Long-term hydromechanical behaviour of a deep cavity taking into account a simplified sequence of life stages. (April 2023) - Sun, Y.; Wong, H.; Pardoen, B.; Deleruyelle, F.; Dufour, N.
Abstract: This study first presents an analytical approach for the hydromechanical behaviour of a deep spherical cavity during different stages of its simplified life cycle. The underground cavity is assumed to be excavated in a dilatant poro-viscoplastic rock mass, and viscoplasticity is modelled based on the Perzyna's overstress concept. The dilation is incorporated by assuming that the volumetric viscoplastic strain rate is a linear function of the Frobenius norm of the deviatoric plastic strain rate. Some numerical examples are performed to examine the applicability of the model. Then, a sensitivity analysis is conducted on the time-dependent development of the Excavation Damaged Zone (EDZ) around an unsupported deep cavity. The von Mises equivalent strain is used as a criterion to assess the time–dependent extension of the damaged area. The conclusions provide some useful guidelines for the engineering design of underground openings.